Usefulness of Adalimumab in the Treatment of Refractory Uveitis Associated with Juvenile Idiopathic Arthritis - Carmen García-; Manuel Díaz-Llopis; David Salom; Rosa Bou; Jesus Díaz-Cascajosa; Miguel Cordero-Coma; Gabriela Ortega; Norberto Ortego-Centeno; Marta Suarez-; Juan Cruz-Martínez; Alex Fonollosa; Ricardo Blanco; et al. (Hindawi Limited, 2013)
Purpose. To assess the efficacy and safety of adalimumab in patients with juvenile idiopathic arthritis (JIA) and associated refractory uveitis. Design. Multicenter, prospective case series. Methods. Thirty-nine patients (mean [SD] age of 11.5 [7.9] years) with JIA-associated uveitis who were either not responsive to standard immunosuppressive therapy or intolerant to it were enrolled. Patients aged 13-17 years were treated with 40 mg of adalimumab every other week for 6 months and those aged 4-12 years received 24 mg/m2 body surface. Results. Inflammation of the anterior chamber (2.02 [1.16] versus 0.42 [0.62]) and of the posterior segment (2.38 [2.97] versus 0.35 [0.71] decreased significantly between baseline and the final visit (P<0.001). The mean (SD) macular thickness at baseline was 304.54 (125.03) μ and at the end of follow-up was 230.87 (31.12) μ (P<0.014). Baseline immunosuppression load was 8.10 (3.99) as compared with 5.08 (3.76) at the final visit (P<0.001). The mean dose of corticosteroids also decreased from 0.25 (0.43) to 0 (0.02) mg (P<0.001). No significant side effects requiring discontinuation of therapy were observed. Conclusion. Adalimumab seems to be an effective and safe treatment for JIA-associated refractory uveitis and may reduce steroid requirement.